Proposing an Affordable Real-Time Camera-Based Safety and Quality Management Framework for Construction Industries in Developing Countries - Zanyar Omar Abdullah; Tahir Çelik; Tolga Çelik (Buildings)
The construction industry in developing countries faces persistent challenges, including limited funding, poor infrastructure, insufficient use of technology, and weak quality management practices. These issues reduce productivity, compromise safety, and lower efficiency, often resulting in project delays, cost overruns, and substandard structures. This study introduces a safety and quality management framework that uses affordable camera technology and a structured web-based platform to address these challenges. The proposed system is designed to identify, document, and resolve potential issues systematically, fostering safer and more efficient construction environments. This research addresses the gap between the potential of technological advancements and their limited adoption in resource-constrained settings. Financial barriers often limit the availability of expertise on-site and restrict access to sophisticated tools, while inadequate quality control exacerbates risks, wastes resources, and undermines project outcomes. By introducing an affordable, easy-to-deploy solution, this study aims to bridge that gap and improve industry practices. Initial case studies have demonstrated promising results, including achieving acceptable quality and safety levels through the help of expertise from abroad. This paper details the design, implementation, and scalability of the proposed system while highlighting its adaptability to diverse construction contexts in developing nations. Additionally, it emphasizes the broader benefits of integrating technology into the construction industry, such as promoting economic growth and supporting sustainable development. Adopting this high-impact, cost-effective solution has the potential to significantly enhance technical capabilities, improve efficiency, and elevate social conditions through safer and more sustainable construction practices. This framework represents a transformative opportunity for the construction industry in developing countries, contributing to long-term progress and prosperity.